Duration of viable virus shedding and polymerase chain reaction positivity of the SARS-CoV-2 Omicron variant in the upper respiratory tract: a systematic review and meta-analysis. (April 2023) - Wu, Yu; Guo, Zirui; Yuan, Jie; Cao, Guiying; Wang, Yaping; Gao, Peng; Liu, Jue; Liu, Min
Highlights: The duration of viable virus shedding of the Omicron variant was 5.16 days. The average duration of polymerase chain reaction positivity of the Omicron variant was 10.82 days. The duration in symptomatic patients was higher than that in asymptomatic patients. Some studies found a difference between the Omicron and Delta variant infections. Abstract: Objectives: To assess the duration of viable virus shedding and polymerase chain reaction (PCR) positivity of the SARS-CoV-2 Omicron variant in the upper respiratory tract. Methods: We systematically searched PubMed, Cochrane, and Web of Science for original articles reporting the duration of viable virus shedding and PCR positivity of the SARS-CoV-2 Omicron variant in the upper respiratory tract from November 11, 2021 to December 11, 2022. This meta-analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and was registered with PROSPERO (CRD42022357349). We used the DerSimonian-Laird random-effects meta-analyses to obtain the pooled value and the 95% confidence intervals. Results: We included 29 studies and 230, 227 patients. The pooled duration of viable virus shedding of the SARS-CoV-2 Omicron variant in the upper respiratory tract was 5.16 days (95% CI: 4.18-6.14), and the average duration of PCR positivity was 10.82 days (95% CI: 10.23-11.42). The duration of viable virus shedding and PCR positivity of the SARS-CoV-2 Omicron variant in symptomatic patients was slightly higher than that in asymptomatic patients, but the difference was not significant ( P >0.05). Conclusion: The current study improves our understanding of the status of the literature on the duration of viable virus shedding and PCR positivity of Omicron in the upper respiratory tract. Our findings have implications for pandemic control strategies and infection control measures.